ASYMMETRIC-SYNTHESIS OF BOTH ENANTIOMERS OF PYRROLIDINOISOQUINOLINE DERIVATIVES FROM L-MALIC ACID AND L-TARTARIC ACID - LEE, YS; KANG, DW; LEE, SJ; PARK, H (AMER CHEMICAL SOC, 1995)
The pyrrolidinoisoquinoline derivatives ((-)-3, (-)-4) and their antipodes ((+)-3, (+)-4) were prepared by reductive deoxygenation and reduction from the intermediates 9 and 10. The key intermediates 9 and 10 were prepared by a diastereoselective N-acyliminium ion cyclization of chiral lactams, which derived from L-malic acid and L-tartaric acid, respectively.